The biodiversity of the genus is berberis l. in Kyrgyzstan (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article provides a morphological description of the species of the genus Berberis found in Kyrgyzstan, according to their geographical distribution
Keywords: Barabris, berberine, alkaloid, xeromesophyte, biological resource